2018
DOI: 10.3138/cpp.2018-013
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Intensity of Use of Homeless Shelters in Toronto

Abstract: A large administrative data set allows us to examine shelter use by single adults, youth, and families in Toronto. We find important differences in shelter use by single adults, youth, and families. We introduce an approach that allows us to identify a noticeable increase in the percentage of shelter clients whom we define as chronic users of the shelter system—people for whom each episode of shelter use is typically very long. This should be a concern because chronic users of the system, although they make up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Each episodic user cost the shelter system an average of 1,1039 CAD per year while each chronic user cost 5,311 CAD per year. Similar calculations can be made for Toronto by using the results reported by Jadidzadeh and Kneebone (2018). Assuming the same nightly cost of providing a shelter bed, the calculations reported by those authors imply each youth identified as a transitional user of shelters imposed an annual cost of 646 CAD on the system, or 3.3 times the cost imposed on the shelter system in Calgary.…”
Section: Costingmentioning
confidence: 86%
See 2 more Smart Citations
“…Each episodic user cost the shelter system an average of 1,1039 CAD per year while each chronic user cost 5,311 CAD per year. Similar calculations can be made for Toronto by using the results reported by Jadidzadeh and Kneebone (2018). Assuming the same nightly cost of providing a shelter bed, the calculations reported by those authors imply each youth identified as a transitional user of shelters imposed an annual cost of 646 CAD on the system, or 3.3 times the cost imposed on the shelter system in Calgary.…”
Section: Costingmentioning
confidence: 86%
“…Examples include Culhane et al (2007), who examine family homelessness in four US cities, and Jadidzadeh and Kneebone ( 2018) who examine the use of family shelters in Toronto. To our knowledge, the only applications of k-mean cluster analysis to describe the patterns and intensity of homeless shelter use by youth is this current study and that of Jadidzadeh and Kneebone (2018) who examine data describing shelter use in Toronto.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation